Teacher-pupil perceptions and their interactive behaviour in the classroom - Mahyuddin, Rahil (1982)
This study attempts to find out if there were significant differences between the perception of Democratic and Authoritarian teachers towards pupils who were academically good and weak and vice-versa and whether these differences affect their interactions in the classroom. The subjects of this study consisted of standard six teachers who were perceived by their pupils as Democratic and Authoritarian teachers respectively; and pupils who were perceived as academically good or weak by their teachers; from twenty schools in the Federal Territory, Malaysia. Both teachers and pupils were randomly selected. The grouping of teachers into Democratic and Authoritarian types was done by using questionnaires modified from statements prepared by Flanders. The questionnaires were answered by pupils. The perceived Democratic and Authoritarian teachers were interviewed using a prepared questionnaire on the perception of their pupils using the bi-polar construct of academically good and academically weak . Ten Democratic and ten Authoritarian teachers were chosen. Four hundred pupils were also chosen basing on their teachers 'perception of their academic performance Of these, two hundred were clas sified as academically good and two hundred as academically weak. The observations of the classroom interactions were done through time sampling using regular classroom sessions. The frequency of interactions between pupils and teachers was recorded in prepared recording sheets and computed. A modified Brophy and Good Dyadic Interaction Observation System was used as a guide for scoring. The interact ions were confined to initiatory verbal communication in the classroom. In the analysis of data, two approaches were utilised. The frequency count, and the t-test.